2017
DOI: 10.1111/obr.12658
|View full text |Cite
|
Sign up to set email alerts
|

Promoting healthy food preferences from the start: a narrative review of food preference learning from the prenatal period through early childhood

Abstract: The palatable, energy-dense foods that characterize modern environments can promote unhealthy eating habits, along with humans' predispositions to accept sweet tastes and reject those that are sour or bitter. Yet food preferences are malleable, and examining food preference learning during early life can highlight ways to promote acceptance of healthier foods. This narrative review describes research from the past 10 years focused on food preference learning from the prenatal period through early childhood (ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
41
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 79 publications
3
41
1
3
Order By: Relevance
“…The observed associations between lower BWz and greater eating in the absence of hunger among girls are consistent with prior evidence that IUGR and LBW are associated with greater external and restrained eating, neuronal response to viewing of palatable foods in children, objectively assessed impulsive eating in girls, and sweet taste preference . This study contributes to this growing but still small body of evidence by demonstrating associations between lower birthweight and an objective measure of appetite regulation.…”
Section: Discussionsupporting
confidence: 87%
“…The observed associations between lower BWz and greater eating in the absence of hunger among girls are consistent with prior evidence that IUGR and LBW are associated with greater external and restrained eating, neuronal response to viewing of palatable foods in children, objectively assessed impulsive eating in girls, and sweet taste preference . This study contributes to this growing but still small body of evidence by demonstrating associations between lower birthweight and an objective measure of appetite regulation.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, there was some trend‐level evidence suggesting that initial changes in liking may emerge more quickly during associative conditioning. While exploratory and suggestive at this stage, these findings are consistent with research suggesting that in many cases, simple repeated exposure may be enough (or even superior to associative conditioning 33,41 ) in promoting acceptance, but associative conditioning may play a role in supporting initial changes in liking or willingness to taste, a possibility that warrants further exploration, particularly in subgroups of children who may be less receptive to mere repeated exposure 14,24 . Future research could explore a hybrid approach in which associative conditioning is employed to promote initial tasting, and subsequently followed by repeated exposure to maximize learning effects.…”
Section: Discussionsupporting
confidence: 78%
“…Children's liking of vegetables predicts their vegetable intake, 8‐10 and children can learn to like foods that are available and become familiar 11‐13 . Repeated exposure, in which children taste a target food across several occasions, is one strategy with demonstrated efficacy in increasing children's acceptance of target vegetables 14‐18 . Cooke et al 19 found, for example, when given a disliked target vegetable over 12 daily taste exposures, 4‐to‐6‐year‐old children significantly increased liking for the target vegetable compared with controls, with effects maintained at 1‐month follow‐up.…”
mentioning
confidence: 99%
“…Repeated exposure to sweet foods during CF can enhance children's natural preference for sweet taste, leading to an expectation that food should taste sweet and rejection of foods with other taste profiles [4,5,36,37]. However, repeated exposure to a variety of flavors and textures, including fruits and vegetables, increases acceptance of new and previously rejected foods and flavors [4].…”
Section: Discussionmentioning
confidence: 99%